أثر استخدام السلع الوسيطة المستوردة على تركيبة الصادرات (صادرات دول جنوب شرق آسيا) - خالدي, أبوبكر; عبيدلي, عبد القادر (جامعة الوادي - University of Eloued, 2022)
This study aims to measure the impact of the use of imported intermediate goods on the composition of Southeast Asian countries exports, represented in the exports of China and India, Indonésie, Malaisie, Philippines, Thaïlande, Singapour during the period (1995-2018), using the index of domestic value added in exports (DVA) as a dependent variable, expressing the composition of exports, and the indexes of the imports of intermediate goods (IMGR_INT), the foreign value added in exports (FVA), the foreign investment inflows (FDI) and the freedom of trade(TF) as independent variables, expressing the use of imported intermediate goods, in the context of trade liberalization. The study achieves, after the data treatment with the stata14 program and using the Autoregressive Distributed Deceleration Model (PMG/ARDL), that there is a long-term causal relationship between the dependent variable and the independent variables. The relationship between the dependent variable and the independent variables of the imports of intermediate goods (IMGR_INT), foreign value added in exports (FVA) and foreign inflows of investment (FDI), is positive, except for the independent variable, freedom of trade (TF), which has an inverse relationship
The impact of the use of imported intermediate goods on exports of Asian Southeast Countrie
مقالl
Keywords: السلع الوسيطة ; القيمة المضافة المحلية في الصادرات ; الروابط الأمامية ; الروابط الخلفية